2014
DOI: 10.1371/journal.pone.0101468
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Exerts Neuroprotective Effects against Experimental Parkinson’s Disease

Abstract: In clinical practice, deep brain stimulation (DBS) is effective for treatment of motor symptoms in Parkinson’s disease (PD). However, the mechanisms have not been understood completely. There are some reports that electrical stimulation exerts neuroprotective effects on the central nervous system diseases including cerebral ischemia, head trauma, epilepsy and PD, although there are a few reports on neuroprotective effects of spinal cord stimulation (SCS). We investigated the neuroprotective effects of high cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Following these initial studies, other laboratories have independently validated our animal findings . In parallel, during the past 7 years, several independent clinical studies in PD patients with abnormal posture and gait disturbances have demonstrated positive results with DCS …”
supporting
confidence: 54%
See 1 more Smart Citation
“…Following these initial studies, other laboratories have independently validated our animal findings . In parallel, during the past 7 years, several independent clinical studies in PD patients with abnormal posture and gait disturbances have demonstrated positive results with DCS …”
supporting
confidence: 54%
“…Remarkably, such a neuroprotective effect was achieved by delivering DCS for 30 minutes, twice a week only, suggesting that better effects could be produced by more frequent therapy. These results have now been replicated independently by another laboratory, which reported that 1 hour/day of DCS, delivered for 16 consecutive days, resulted in the improvement of PD symptoms and the significant preservation of tyrosine hydroxylase (TH) fibers in the striatum and TH‐positive neurons in the SNc. Although the cellular mechanism underlying this putative long‐term neuroprotective action of DCS remains to be investigated, Shinko and colleagues also reported that DCS treatment upregulated the levels of vascular endothelial growth factor, a finding that could account, at least partially, for the observed neuroprotective effects.…”
Section: Preliminary Evidence Of Neuroprotectionmentioning
confidence: 75%
“…The vasodilation at 500 Hz stimulation is caused by the activation of fibers that contain TRPV1 and the release of CGRP . Another animal study with a Parkinson's Disease rat model showed that the application of high cervical SCS increased levels of VEGF in the lesioned striatum and thereby exerting its neuroprotective effects . Furthermore, the neuroprotective effects seemed optimal with 50 Hz SCS when compared with 2 Hz and 200 Hz SCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the protective effects of SCS postconditioning at two frequencies (2 Hz and 50 Hz) were assessed. The 50 Hz SCS was selected because it is conventionally used in both clinical and experimental studies of pain treatment and has also been reported to augment cerebral blood flow markedly , reduce stroke volume in permanent middle cerebral artery (MCA) occlusion rats , inhibit myocardial apoptosis and reduce expression of caspase‐3 after cardiac ischemia/reperfusion , and ameliorate Parkinson symptoms and immunohistochemical changes in Parkinson's disease (PD) rats. Low frequency SCS (below 5 Hz) has also been used in researches.…”
Section: Discussionmentioning
confidence: 99%